Determination of Prevalence, Predictors and Effects of Dysmenorrhoea among Adolescent Girls - A Cross-sectional Study - Varadaneshwari SK; Shilpa N Kugali; Deelip S Natekar; Reshma S; Basanagouda Patil; Mallikarjun .; Jayashree .; Jyothi .; Anjana .; Kiran . (RGUHS Journal of Nursing Sciences)
Background Dysmenorrhoea is a common gynaecological issue. It has been predominant among women in their late teenage and early twenties and normally declines with age. It likewise influences over 80 of ladies in their conceptive age.Method A cross-sectional non-exploratory research was conducted in a provincial area of Bagalkot region. The researcher randomly chose Shirur town as the provincial setting for the enrolment of subjects. All the young women in the age group of 12-18 years were included in the study. The socio-demographic variables were collected from each participant. The data were analyzed using descriptive and inferential statistics.Result The prevalence of dysmenorrhea was found to be 68.1 95 CI 65.0 with a majority of respondents reporting severe aggravation. Additionally 22.5 of participants reported adverse impacts on their daily activities during menstruation. Teenagers who didnt live with their parents experienced a prevalence of 53.1. Moreover respondents with irregular periods reported a prevalence of 72.5.Conclusion A significant relationship between sporadic monthly cycle p lt0.01 not living with their parent p lt 0.04 and self-reported dysmenorrhoea was noted.